Determining the role of music attitude and its precursors in stimulating the psychological wellbeing of immigrants during COVID quarantine – a moderated mediation approach - Wang, Xiaokang; Huang, Wenrong (Frontiers in Psychology, 2023)
Based upon social cognitive theory (SCT), the purpose of this study is to examine the role of music attitude and its essential precursors stimulating psychological wellbeing of multicultural individuals in isolation (quarantine) during COVID pandemic. This study employed quantitative methodology; a survey was administered online to collect sufficient data from 300 immigrants (multicultural individuals) who traveled to China during the pandemic. Due to the respondents' diverse nationalities, languages, cultures, and norms, they were designated as multicultural individuals. Sufficient data has been collected from 5 centralized quarantine centers situated in different cities in China. In addition, the valid data set was analyzed using structural equation modeling (SEM) via AMOS 24 and SPSS 24. The results indicate that the potential predictors such as cognitive  music experience (MEX), environmental  social media peer influence (SPI) & cultural factorsnative music (NM) have a direct, significant and positive effect on music attitude (MA) which further influences multicultural individuals’ psychological well being (PW) during their quarantine period. Besides, in the presence of the mediator (MA), the mediating relationships between MEX and PW and NM and PW are positive, significant and regarded as partial mediation. Whereas, the moderated mediation effects of music type (MT) on MEX-MA-PW and NM-MA-PW were found to be insignificant and unsupported. This study contributes to the literature on the effectiveness of individuals’ music attitude and its associated outcomes, focusing on persons’ mental health care in a loneliness situations such as quarantine during COVID pandemic time. Much importantly, this study has raised the awareness about music, music attitude and its fruitful outcomes in the form of mental calmness and peacefulness to the general public or masses, particularly during social distancing, isolation and quarantine in COVID pandemic situation.